Everybody to Count for One? Inclusion and Exclusion in Welfare-Consequentialist Public Policy - Semple, Noel (2019)
This article asks which individuals should count in welfare-consequentialist analysis of public policy. Possible answers to this question fall along a spectrum between parochial and inclusive. The most parochial impartial answer is that only welfare effects experienced by the living human subjects of a government should be considered in analysis of its policy options. At the other end of the spectrum, the most inclusive answer would be that welfare impacts on all individuals who are capable of having welfare should be weighed equally. A two-level response to the “who counts” question is proposed. A specification of welfare-consequentialism serving as an ethical ideal might give equal weight to non-human individuals, to foreigners, and to the unborn. However, a welfare-consequentialist decision procedure must take into account the error-proneness of human analysts’ welfare predictions. Predictions of a policy’s welfare impacts on individuals who are more dissimilar from the predicting government are more likely to be wrong, compared to predictions regarding living human subjects. The paper concludes by considering alternative answers to the “who counts” questions that might minimize the combined rate of exclusion and misprediction errors.
Keywords: Noel Semple